EFFECT OF LONG-TERM POLYPHARMACY AND THE DRUG BURDEN INDEX (DBI) ON CARDIAC FUNCTION AND FIBROSIS IN AGED MICE. (11th November 2018) - Tran, T; Mach, J; Gemikonakli, G; Howlett, S; deCabo, R; Le Couteur, D; Hilmer, S
Abstract: Polypharmacy (use of ≥ 5 medications) and Drug Burden Index (DBI: measures cumulative exposure to anticholinergic and sedative drugs) impair function in older adults. Preclinical studies can provide a mechanistic understanding. We aim to evaluate the effect of chronic polypharmacy, medications with increasing DBI and deprescribing (cessation of medications) on cardiac function and histology in aged mice. Twelve-month-old male C57BL/6 mice received control feed or feeds/water containing therapeutic doses of drugs in regimens of polypharmacy with Zero DBI (simvastatin, metoprolol, omeprazole, paracetamol, irbesartan), Low DBI (simvastatin, metoprolol, omeprazole, paracetamol, citalopram), High DBI (simvastatin, metoprolol, oxybutynin, oxycodone, citalopram) or monotherapy with each of the five drugs from the High DBI diet. At 21 months, animals were re-randomised to continue treatment or be deprescribed. Blood pressure (BP) and rotarod performance (endurance) were assessed every 3 months and hearts were collected at 27 months. Compared to control, we observed a significant decrease in systolic and diastolic BP in Zero DBI, Low DBI, metoprolol and simvastatin treated mice and not in High DBI treated mice at 21 months (p<0.05). On rotarod performance, latency-to-fall declined in mice administered citalopram, compared to control (p<0.05) at all time points, with non-significant improvement after deprescribing. Preliminary histology (n=3) suggests a non-significant trend towards increased myocardial fibrosis in High DBI mice. Our results indicate that chronic High DBI diet may impair therapeutic effects of cardiac drugs and increase cardiac collagen. Citalopram reduces endurance and it can be reversed with deprescribing. Future studies will continue to address histological changes involved.